2017
DOI: 10.1016/j.jand.2016.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Physics of Functional Fibers in the Gastrointestinal Tract: An Evidence-Based Approach to Resolving Enduring Misconceptions about Insoluble and Soluble Fiber

Abstract: Enduring misconceptions about the physical effects of fiber in the gut have led to misunderstandings about the health benefits attributable to insoluble and soluble fiber. This review will focus on isolated functional fibers (eg, fiber supplements) whose effects on clinical outcomes have been readily assessed in well-controlled clinical studies. This review will also focus on three health benefits (cholesterol lowering, improved glycemic control, and normalizing stool form [constipation and diarrhea]) for whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
292
1
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 388 publications
(312 citation statements)
references
References 117 publications
8
292
1
11
Order By: Relevance
“…These results also confirmed that SDF was more viscous and adsorbable. The viscosity of SDF was related to many functional properties, such as lowering serum cholesterol and improving glycemic control and intestinal fermentation …”
Section: Resultsmentioning
confidence: 99%
“…These results also confirmed that SDF was more viscous and adsorbable. The viscosity of SDF was related to many functional properties, such as lowering serum cholesterol and improving glycemic control and intestinal fermentation …”
Section: Resultsmentioning
confidence: 99%
“…Mucilage showed 28% and 8% more water‐ and oil‐holding capacities than pectin, respectively. Comparing mucilage and pectin behavior, it was shown that mucilage consumption causes clinically meaningful health benefits as cholesterol lowering, improving glycemic control, effects highly correlated with the viscosity of soluble fibers; increasing with water‐holding capacity …”
Section: Chemical Composition Changes Of Cactus Stemsmentioning
confidence: 99%
“…In the hind-gut, the physiological benefits of fibre are believed to arise from the products of bacterial fermentation of the soluble fibre, and from the physicochemical properties of any fibre that remains unfermented [59, 60]. Among the most important physicochemical properties of kiwifruit fibres are the hydration properties, which include water retention, capacity and swelling, viscosity (which requires solubility), and properties that depend on the size, shape and porosity of undigested particles.…”
Section: The Nutritional Attributes Of Kiwifruitmentioning
confidence: 99%
“…Among the most important physicochemical properties of kiwifruit fibres are the hydration properties, which include water retention, capacity and swelling, viscosity (which requires solubility), and properties that depend on the size, shape and porosity of undigested particles. Water retention is physiologically relevant because it influences transit time, faecal bulk, stool consistency and other functional benefits [60]. The high swelling and water retention of kiwifruit fibre in comparison with other forms of dietary fibre such as wheat bran, commercial preparations of sugar beet fibre and apple fibre, accentuate the value of consuming kiwifruit as a natural whole product that has had minimal processing.…”
Section: The Nutritional Attributes Of Kiwifruitmentioning
confidence: 99%